Resident Front Office Experience: A Systems-Based Practice Activity - Sutkin, Gary (Medical Education Online, 2008)
PURPOSE: We set out to create and evaluate a systems-based practice experience designed to introduce residents to front office responsibilities and stimulate suggestions for front office improvements. METHODS: On two occasions in 2002 and 2006, each resident in the Obstetrics and Gynecology Department was trained by a front office staff member for one day. The residents completed pre- and post-experience surveys, answered open-ended questions about their experience, and volunteered suggestions for improving the front office staff, and were evaluated by their precepting staff member. RESULTS: All but two of 23 particpating residents participated enthusiastically. These residents perceived experiencing the staff as vital to the success of the practice, reported an increased sense of appreciation for the training of staff personnel, and were evaluated favorably. CONCLUSION: This program gave our residents an appreciation for the training and responsibilities of pivotal office staff and an opportunity to suggest improvements. This program also satisfied ACGME resident education requirements regarding systems-based practice.